Scalpel or Sheath? Outcomes Comparison Between Pre-Peritoneal Pelvic Packing and Angioembolization for Definitive Hemorrhage Control After REBOA - Brenner, Megan; Moore, Laura; Zakhary, Bishoy; Schwed, Alexander; Cralley, Alexis; Romagnoli, Anna; Fox, Charles; Scalea, Thomas; Burlew, Clay Cothren (Journal of Endovascular Resuscitation and Trauma Management, 2020)
Background: The role of angioembolization (AE) and pre-peritoneal pelvic packing (PPP) for pelvic hemorrhage control in the era of resuscitative endovascular balloon occlusion of the aorta (REBOA) has not been well described. Our aim was to investigate outcomes of PPP and AE after REBOA. Methods: Patients who received aortic occlusion (AO) at Zone 3 (distal abdominal aorta) plus PPP and/or AE at three high-volume REBOA centers between February 2013 and December 2018 were identified. Outcomes were compared between three groups based on procedures performed: REBOA with PPP only (RPPP), REBOA with angioembolization only (RAE), and REBOA with PPP and AE (RPPPAE). Results: Fifty-eight patients underwent REBOA at Zone 3; 37 RPPP, 13 RAE, 8 RPPPAE. Mean age was 45 ± 16 years, mean injury severity score (ISS) 35 ± 13, mean systolic blood pressure (SBP) pre-AO was 71 ± 19 mmHg, and post-AO SBP was 110 ± 34 mmHg. In-hospital mortality was 28%, with the majority of deaths occurring in the intensive care unit. Age, ISS, admission SBP, physiology on admission and at the time of AO, response to AO, admission hemoglobin, blood products transfused, and rate of local wound infections were not different between RPPP and RAE groups. Comparing RPPP to RAE groups, duration of AO was significantly lower in the RPPP group (45 + 34 vs 81 + 37 mins, p = 0.012), while rates of acute kidney injury (14% vs 46%) and distal embolism (8% vs 31%) were higher in the RAE group (p = 0.015, 0.04, respectively).There was no statistical difference in mortality between RPPP (22%) and RAE patients (39%), including on regression analysis controlling for duration of AO and ongoing CPR at the time of AO. Conclusion: Despite a longer duration of AO and higher rates of ongoing CPR at the time of AO in RAE patients, mortality rates are similar whether hemostasis is achieved after REBOA with pelvic packing or angioembolization. RPPP results in significantly lower systemic and local complication rates.